SATUAN POLISI PAMONG PRAJA WANITA DALAM MENJALANKAN TUGAS DAN PERAN PUBLIKNYA - Srifarika Srifarika; Wa Ode Winesty (KABANTI : Jurnal Kerabat Antropologi, 2023)
This research aims to know and describe the female Pamong Praja Police Unit in carrying out their public duties and roles, as well as to understand and describe the female Pamong Praja Police Unit in carrying out their domestic duties and roles, especially in Kendari City. The results showed that female Satpol PP members or Srikandi Pol PP Kendari City have dual roles. The dual roles in question are public roles and domestic roles. In carrying out their public role, Srikandi Pol PP has various experiences in serving in the field, especially when carrying out the process of controlling street vendors. During the curbing process, they often get cursed and even violence. However, this does not make them give up or get tired of their work. This becomes a reference for them to be better at work and still prioritize the humanist side. Srikandi Pol PP also carries out their domestic duties and roles, namely as housewives. The domestic roles undertaken by Srikandi Pol PP are in the form of household chores such as cooking, taking care of children, cleaning the house, washing, ironing and taking care of plants. In addition, they also run small businesses from home to increase their income.